2019
DOI: 10.1002/acm2.12756
|View full text |Cite
|
Sign up to set email alerts
|

Calculating dose from a 2.5 MV imaging beam using a commercial treatment planning system

Abstract: Patient dose from 2.5 MV images on the TrueBeam linear accelerator is not easily quantified, primarily because this beam energy is not normally modeled by commercial treatment planning systems. In this work we present the feasibility of using the Eclipse® treatment planning system to model this beam. The Acuros XB and the AAA dose calculation algorithms were tested. Profiles, PDDs, and output factors were measured for the 2.5 MV unflattened imaging beam and used for beam modeling. The algorithms were subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The 2.5 MV beam has a peak and mean energies of around 120 and 500 keV, respectively, 17,19 compared to 1 and 1.5 MeV, 41 respectively, for a 6 MV beam. The considerable amount of low-energy photons in the 2.5 MV beam can lead to a dose enhancement if used in combination with gold nanoparticles (GNPs).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The 2.5 MV beam has a peak and mean energies of around 120 and 500 keV, respectively, 17,19 compared to 1 and 1.5 MeV, 41 respectively, for a 6 MV beam. The considerable amount of low-energy photons in the 2.5 MV beam can lead to a dose enhancement if used in combination with gold nanoparticles (GNPs).…”
Section: Discussionmentioning
confidence: 99%
“…The study also demonstrated a sharp dose fall-off for carbon target percentage depth dose (PDD) measured in water. Other studies [18][19][20] have been performed for characterizing the physical properties of the lowenergy photons such as PDDs, dose profiles, and energy spectrum for 2.5 MV from a TrueBeam machine. Some of them 19,20 evaluated the dose to patient of the 2.5 MV imaging photons through commissioning and modeling of the beam.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations